The museum of Chora : mosaics and frescoes - Akit, Ilhan (Istanbul : Aksit kultur turizm sanat ajans, 1997)
Overzich van de mozaïeken en de fresco's
Keywords: Museum of Chora [Istanboel].; Collectiecatalogus; Iconografie